Dolutegravir pharmacokinetics during co-administration with either artemether/lumefantrine or artesunate/amodiaquine. (7th February 2021) - Kawuma, Aida N; Walimbwa, Stephen I; Pillai, Goonaseelan (Colin); Khoo, Saye; Lamorde, Mohammed; Wasmann, Roeland E; Denti, Paolo
Abstract: Background: In sub-Saharan Africa, artemisinin-containing therapies for malaria treatment are regularly co-administered with ART. Currently, dolutegravir-based regimens are recommended as first-line therapy for HIV across most of Africa. Objectives: To investigate the population pharmacokinetics of dolutegravir during co-administration with artemether/lumefantrine or artesunate/amodiaquine, two commonly used antimalarial therapies. Methods: We developed a population pharmacokinetic model of dolutegravir with data from 26 healthy volunteers in two Phase 2 studies with a total of 403 dolutegravir plasma concentrations at steady state. Volunteers received 50 mg of dolutegravir once daily alone or in combination with standard treatment doses of artemether/lumefantrine (80/480 mg) or artesunate/amodiaquine (200/540 mg). Results: A two-compartment model with first-order elimination and transit compartment absorption best described the concentration–time data of dolutegravir. Typical population estimates for clearance, absorption rate constant, central volume, peripheral volume and mean absorption transit time were 0.713 L/h, 1.68 h −1, 13.2 L, 5.73 L and 1.18 h, respectively. Co-administration of artemether/lumefantrine or artesunate/amodiaquine increased dolutegravir clearance by 10.6% (95% CI 4.09%–34.5%) and 26.4% (95% CI 14.3%–51.4%), respectively. Simulations showed that simulated trough concentrations of dolutegravir alone or in combination with artemether/lumefantrine or artesunate/amodiaquine are maintained above the dolutegravir protein-adjusted IC90 of 0.064 mg/L for more than 99% of the individuals. Conclusions: Dolutegravir dose adjustments are not necessary for patients who are taking standard 3 day treatment doses of artemether/lumefantrine or artesunate/amodiaquine.